The potential of golden apple snail (Pomacea canaliculata) meat meal as an alternative protein source for juvenile Chinese mitten crab (Eriocheir sinensis) - Wenxiang Yao; Chunyan Zhang; Rui Jia; Rui Jia; Sitong Zhao; Weibo Jiang; Guoan Hua; Sizhe Zhao; Apeng Lin; Jianguo Wang; Quan Wang (Frontiers in Marine Science)
This study investigated the effects of replacing dietary fish meal (FM) with golden apple snail (Pomacea canaliculata) meat meal (PCM) on growth performance, non-specific immunity and intestinal health of juvenile Chinese mitten crab (Eriocheir sinensis). Four hundred juvenile Chinese mitten crabs (2.39 ± 0.03) g were randomly distributed into five groups in quadruplicate (20 crabs per tank), and each group was fed with diets that replaced FM with PCM at 0% (FM-20, containing 200 g/kg FM), 25% (FM-15), 50% (FM-10), 75% (FM-5), and 100% (FM-0) for 8 weeks, respectively. The results showed that the growth, whole body composition, digestive enzyme activities, antioxidant performance, non-specific immunity, intestinal histology and microbiota composition of FM-15 and FM-10 groups all reached the same level as the FM-20 group (P > 0.05). While the replacement ratio reached 75%, the FCR was significantly increased and the peritrophic membrane thickness was significantly decreased (P< 0.05). When 100% FM was replaced, significantly decreased the growth performance, serum antioxidant and immune enzyme activities, mid-intestine folds height, width and the peritrophic membrane thickness (P< 0.05), and significantly increased the abundance of intestinal harmful bacteria Vibrio (P< 0.05). In conclusion, PCM can effectively replace 50% dietary FM (100 g/kg) without negative effects on the growth performance, intestinal health, serum immune, and antioxidant indexes of juvenile E. sinensis.